Neodymium iron boron magnet and its preparation method and application

By regulating the distribution and sintering process of elements such as CU, GA, Al, prepare high -performance tin iron boron magnets, solve the problem of traditional magnets relying on heavy rare earth elements, realize the improvement of high remaining magnets and stubborn performance, while reducing the reduction Production cost.

CN114284018BActive Publication Date: 2025-01-28YANTAI ZHENGHAI MAGNETIC MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111616641.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-27
Publication Date
2025-01-28
Estimated Expiration
2041-12-27

AI Technical Summary

Technical Problem

When traditional sintered NdFeB magnets improve coercive performance, they rely on heavy rare earth elements, resulting in increased resource consumption and production costs, while reducing the residual magnetic and magnetic field strength of the magnet, limiting the lightweight and miniaturization of the device.

Method used

By regulating the distribution ratio of elements such as CU, GA, AL and the distribution in the magnet, combined with more than three sections of sintering insulation process and timeliness processing, prepare high -performance 钕 iron boron magnets with R2 (Fe, M) 14B structure , Inhibit the abnormality of the main phase grain, increase the density and direction of the magnet.

Benefits of technology

The preparation of high -performance 硼 iron boron magnets is realized, the magnetic (BR) and orthodox (HCJ) performance of the magnet are improved, the use of heavy rare earth elements is reduced, and the comprehensive performance of production efficiency and magnetic body is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114284018B_ABST
    Figure CN114284018B_ABST
Patent Text Reader

Abstract

The present invention provides a neodymium iron boron magnet and a preparation method and application thereof, wherein the magnet comprises a NdFeB magnet having R2(Fe, M) 14 The main phase grains and grain boundary phase of the B structure; the grain boundary phase includes two grain boundaries between two main phase grains and a triangular grain boundary composed of three or more main phase grain gaps; wherein M includes Cu, Ga, and / or Al, and R is at least one rare earth element including Nd. The present invention can obtain a higher Br and Hcj of the magnet by adjusting the composition ratio of elements such as Cu, Ga, Al and their distribution in the magnet, as well as the grain size.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of NdFeB magnets, and in particular relates to a sintered NdFeB magnet and a preparation method and application thereof. Background Art

[0002] Sintered NdFeB permanent magnet material is the most widely used permanent magnet functional material with the highest comprehensive magnetic properties. It is known as the contemporary "King of Magnets" and is a key supporting material for promoting the development of energy, information and other related fields. Since its advent in the 1980s, sintered NdFeB magnets have been widely used in many fields such as the automotive industry, medical equipment, electronic information, aerospace, etc. due to their excellent magnetic properties and extremely high cost performance, becoming a key support for the development of related fields towards intelligence, miniaturization and lightweight. In recent years, with the continuous improvement of the performance of sintered NdFeB magnets, its application areas are also constantly expanding.

[0003] In order to ensure stable magnetic field output under high temperature conditions, sintered NdFeB permanent magnet materials need to have high coercive force performance. Traditionally, heavy rare earth Dy / Tb raw materials are added in the smelting process to improve the coercive force of the magnet. Due to the small reserves and high prices of heavy rare earth resources, the large-scale use of heavy rare earth resources is not conducive to the sustainable mining and use of heavy rare earth resources, and also directly leads to a significant increase in the production and manufacturing costs of magnets. In addition, the addition of heavy rare earth metals will reduce the remanence of the magnet, thereby reducing the magnetic field strength provided by the magnet in space, which is not conducive to the lightweight and miniaturization of related devices.

[0004] In order to improve the performance of magnets and reduce the use of heavy rare earths such as terbium and dysprosium, dual alloy technology, grain refinement technology, and grain boundary diffusion technology have attracted the attention of the industry. At present, the most widely used are grain refinement technology and grain boundary diffusion technology. Grain refinement technology is to obtain a smaller air flow grinding particle size by controlling the process parameters of the smelting and powder making process, and matching the corresponding sintering system, and finally achieve the purpose of fine control of magnet particle size, so as to reduce the grain defects inside the magnet and improve the coercive force of the magnet.

[0005] Grain boundary diffusion technology is to coat a layer of diffusion source containing terbium and dysprosium on the surface of the magnet by dipping, spraying, etc. The terbium and dysprosium elements diffuse into the interior of the magnet through the grain boundary phase, and replace the Nd in the neodymium-rich phase in the grain boundary to form (Dy / Tb)2Fe 14 B. Improve the anisotropy at the grain boundaries to achieve the purpose of increasing coercivity.

[0006] Grain refinement technology and grain boundary diffusion technology can be used alone or in combination. In combination, grain refinement technology determines the basis of the final performance of the magnet. With grain refinement technology, the magnet has a fine particle size, a larger surface area of ​​the main phase grains, improved surface energy, and greater activity. Not only is it difficult to eliminate the adsorption of impurity elements C, S, O, and N, resulting in performance degradation, but it is also prone to abnormal grain growth, which in turn deteriorates the magnetic properties. The presence of abnormally grown grains in the magnet will greatly reduce the effect of grain boundary diffusion.

[0007] Patent CN106252012A provides a segmented sintering method to prevent abnormal grain growth, which is to keep the temperature at a constant temperature of 20°C lower than the sintering temperature of the NdFeB magnet for 0-1h, then heat it to the sintering temperature for 3-6h, naturally cool it to between 700-800°C, and then heat it to a temperature 0-20°C higher than the sintering temperature for 5-8h, thereby obtaining a magnet with fine grains and uniform density, and realizing a low heavy rare earth content and high-performance NdFeB magnet. Although the above segmented sintering process is adopted, under the condition of fine grain size, the sintering temperature is high and the segmented insulation time is long, there is still a risk of abnormal grain growth, and the comprehensive sintering cycle is long, and the efficiency of mass production is low. Summary of the invention

[0008] In order to improve the above technical problems, the present invention provides a high-performance NdFeB magnet, the magnet comprising R2(Fe, M) 14 Main phase grains and grain boundary phases of B structure; the grain boundary phase includes two grain boundaries between two main phase grains, and a triangular grain boundary composed of gaps between three or more main phase grains; wherein M includes Cu, Ga, and / or Al, and R is at least one rare earth element including Nd.

[0009] According to an embodiment of the present invention, R includes Nd and also includes at least one selected from the following rare earth elements: Y, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Sc.

[0010] According to the embodiment of the present invention, the average grain size of the main phase grains of the magnet is 1.8-8μm, preferably 2.5-6μm. Within this grain size range, the magnet can obtain better magnetic properties. If the grain size is smaller, less than 1.8μm, the surface activity of the grains is greater, and it is easier to adsorb impurity elements such as O / N, and the adsorbed impurity elements are difficult to remove, resulting in reduced performance; when the grain size is larger, greater than 8μm, the internal structural defects of the main phase grains will increase, and the grain boundary phase is relatively scarce, making it difficult to obtain high-performance NdFeB magnets.

[0011] According to an embodiment of the present invention, the atomic concentration of Cu in adjacent main phase grains is set to [Cu1], and the atomic concentration of Cu in the two-grain boundary is set to [Cu2], which satisfies the relationship of 1≤[Cu2] / [Cu1]<2.

[0012] According to an embodiment of the present invention, the triangular grain boundary in the magnet contains a Cu-rich region, and the atomic concentration of Cu in the triangular grain boundary is set to [Cu3], which satisfies the relationship [Cu3] / [Cu1]≥2; the grain boundary phase of the Cu-rich region is a non-magnetic phase, and a high content of the Cu-rich region in the magnet will significantly reduce the Br of the magnet. In the triangular grain boundary of the present invention, the region where the Cu element concentration satisfies [Cu3] / [Cu1]≥2 is defined as a Cu-rich region.

[0013] According to an embodiment of the present invention, the Cu-rich region area of ​​the triangular grain boundary accounts for less than 5% of the total grain boundary phase area.

[0014] According to an embodiment of the present invention, the atomic concentration of Ga in adjacent main phase grains is set to [Ga1], and the atomic concentration of Ga in the boundary between two grains is set to [Ga2], which satisfies the relationship of 1≤[Ga2] / [Ga1]<2.

[0015] According to an embodiment of the present invention, the triangular grain boundaries in the magnet contain Ga-rich regions, and the atomic concentration of Ga in the triangular grain boundaries is set to [Ga3], which satisfies the relationship [Ga3] / [Ga1]≥2, that is, in the triangular grain boundaries, the region where the Ga element concentration satisfies [Ga3] / [Ga1]≥2 is defined as a Ga-rich region, and the grain boundary phase of the Ga-rich region is a non-ferromagnetic phase. Preferably, the area of ​​the Ga-rich region in the triangular grain boundaries accounts for <5% of the total area of ​​the grain boundary phase.

[0016] According to an embodiment of the present invention, the atomic concentration of Al in adjacent main phase grains is set to [Al1], and the atomic concentration of Al in the grain boundary between two grains is set to [Al2], which satisfies the relationship of 1<[Al2] / [Al1]<2.

[0017] According to an embodiment of the present invention, the triangular grain boundaries in the magnet contain Al-rich regions, and the atomic concentration of Al in the triangular grain boundaries is set to [Al3], which satisfies the relationship [Al3] / [Al1]≥2, that is, in the triangular grain boundaries, the region where the Ga element concentration satisfies [Al3] / [Al1]≥2 is defined as an Al-rich region, and the grain boundary phase of the Al-rich region is a non-magnetic phase. Preferably, the area of ​​the Al-rich region in the triangular grain boundaries accounts for <5% of the total area of ​​the grain boundary phase.

[0018] In the present invention, the adjacent main phase grains refer to the main phase grains adjacent to the two-grain boundary.

[0019] In the traditional magnet manufacturing process, Cu hardly enters the main phase grains, but mainly concentrates in the Nd-rich phase at the grain boundary, achieving the effect of improving hcj and improving irreversibility. However, when the Cu content is too high, it will also lead to the reduction of Br and Hcj performance; a small amount of Al occupies the 8j2 crystal position in the main phase grains, making the grains refined, and most of Al reduces the agglomerate distribution of the Nd-rich phase and the B-rich phase at the grain boundary, improving the wetting angle with the main phase, and making the Nd-rich phase more uniformly distributed along the boundary; a small amount of Ga exists in the main phase grains, mainly enriched in the grain boundary, achieving the effect of refining the grains and improving the wettability of the grain surface, but because the compound formed by it is a non-ferromagnetic phase, it will irreversibly reduce Br due to the addition of Cu / Ga / Al, etc. Further, these stable compounds are enriched in the surface of the grains, inhibiting the replacement reaction of heavy rare earth elements such as Dy / Tb on the surface component structure of the grains during the diffusion process, which directly leads to a significant reduction in the diffusion Hcj increase.

[0020] According to an embodiment of the present invention, [Cu2] / [Cu1] is greater than or equal to 1 and less than 2, and more preferably 1.2-1.8. Within this atomic concentration ratio range, Cu is relatively evenly distributed in the surface layer of the main phase grains and in the grain boundaries between the two grains; Ga and Al also show the same rule.

[0021] According to an embodiment of the present invention, the high-performance NdFeB magnet further includes transition metal elements, such as Mn, Si, Zr, Ti, Nb, etc. The transition metal elements are enriched in the grain boundary phase. When the magnet has a distribution pattern similar to that of Cu, Ga, and Al, that is, 1≤[Zr2] / [Zr1]<2, and / or 1≤[Ti2] / [Ti1]<2, and / or 1≤[Nb2] / [Nb1]<2, a high-performance magnet can be obtained. Wherein, [Zr1] represents the atomic concentration of Zr in adjacent main phase grains, and [Zr2] represents the atomic concentration of Zr in the grain boundary between two grains; [Ti1] represents the atomic concentration of Ti in adjacent main phase grains, and [Ti2] represents the atomic concentration of Ti in the grain boundary between two grains; [Nb1] represents the atomic concentration of Nb in adjacent main phase grains, and [Nb2] represents the atomic concentration of Nb in the grain boundary between two grains.

[0022] According to an embodiment of the present invention, the high-performance NdFeB magnet comprises the following components based on a mass ratio of 100%:

[0023] 27-35% R; R is at least one rare earth element including Nd;

[0024] 0.8-1.2wt% B;

[0025] 0-3.0wt%Co;

[0026] 0.1-0.6wt%Cu;

[0027] 0.1-0.8wt%Ga;

[0028] 0-1.0wt%Al;

[0029] 60-72 wt% T: T includes Fe and other transition metal elements, and inevitable impurity elements, wherein the transition metal elements have the above meanings.

[0030] According to an embodiment of the present invention, R includes Nd and also includes at least one selected from the following rare earth elements: Y, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc. Preferably, R is at least one of Nd, Y, Dy, Tb, Ho, La, Ce; wherein the total mass of Dy, and / or Tb, and / or Ho accounts for ≤5wt% of the total mass of the magnet; the total mass of La, and / or Ce, and / or Y accounts for ≤3wt% of the total mass of the magnet. When R in the magnet is too high, the neodymium-rich phase of the magnet increases and Br decreases; when R is too low, a uniform and continuous Nd-rich phase cannot be formed in the magnet to perform magnetic isolation of the main phase grains, and the Hcj and squareness of the magnet will deteriorate sharply. Because R2(Fe,M) composed of rare earth elements such as Pr, Dy, Tb, Ho 14 The magnetic polarization intensity of the main phase grains of the B series is lower than that of Nd, and the anisotropy field is better than that of Nd, so the Br of the magnet will be significantly reduced and the Hcj will be increased. While ensuring the high Br of the magnet, the Hcj of the magnet can be increased by using a small amount of heavy rare earth elements such as Dy, Tb, and Ho, and their content is ≤5wt% in the total magnet component; the intrinsic magnetic properties of rare earth elements such as La, Ce, and Y are significantly lower than those of Nd, and they are abundant in reserves and low in price, and can also be added in small amounts, and their content is ≤3wt% in the total magnet component. Preferably, R includes Nd and Pr.

[0031] According to the implementation scheme of the present invention, the B content is 0.8-1.2wt%, further preferably 0.87-1.05wt%, and further preferably 0.93-1.00wt%. When the B content is too low, the R content is relatively high, the proportion of the R-rich phase formed is relatively high, and the volume ratio of the main phase grains is small, resulting in a low Br of the magnet, and easily causing the Hcj and squareness of the magnet to be unstable; when the B content is too high, the volume ratio of the B-rich phase is significantly increased, which will greatly reduce the magnetic properties.

[0032] According to the implementation scheme of the present invention, Co will occupy the position of Fe in the main phase grains in the magnet, and the atomic magnetic moment of Co is smaller than that of Fe. Adding Co will reduce the Br of the magnet. At the same time, the addition of Co has a significant effect on the corrosion resistance and temperature resistance of the magnet. Therefore, the Co content is 0-3.0wt%, and 0.5-2wt% is further preferred. When the Co content is 0, its corrosion resistance and temperature coefficient will deteriorate significantly; but when the Co content is greater than 3wt%, its Br will be significantly reduced, and even Hcj will be significantly deteriorated. In addition, high Co will increase the brittleness of the magnet, and it is easy to crack during processing, and the product qualification rate is low. Moreover, Co is a strategic metal and is used in large amounts, which places high demands on the stable supply of raw materials.

[0033] According to the implementation scheme of the present invention, the Cu content is 0.1-0.6wt%, and more preferably 0.2-0.5wt%. When the Cu content is too high, the grain growth will be inhibited, and the grain boundary phase will increase, the volume ratio of the main phase grains will decrease, and the Br of the magnet will be reduced; when the Cu content is too low or even contains no Cu, the main phase grains and B-rich phase of the magnet will be relatively coarse, which will greatly reduce the magnetic properties of the magnet.

[0034] According to the implementation scheme of the present invention, the Ga content is 0.1-0.8wt%, and further preferably 0.2-0.6wt%. When the Ga content is too high, it will inhibit the grain growth, and the grain boundary phase will increase, the volume ratio of the main phase grains will decrease, and the Br of the magnet will be reduced; when the Ga content is too low or even contains no Ga, the main phase grains and B-rich phase of the magnet will be relatively coarse, which will greatly reduce the magnetic properties of the magnet.

[0035] According to the implementation scheme of the present invention, the Al content is 0-1.0wt%, and further preferably 0.1-0.5wt%. When the Al content is too high, the grain growth will be inhibited, and the grain boundary phase will increase, the volume ratio of the main phase grains will decrease, and the Br of the magnet will be reduced; when the magnet does not contain Al, the main phase grains and B-rich phase of the magnet are relatively coarse, which will greatly reduce the magnetic properties of the magnet.

[0036] According to an embodiment of the present invention, T includes Fe and other transition metal elements, and inevitable impurity elements. Other transition metal elements are such as Mn, Si, Zr, Ti, Nb, etc., and inevitable impurity elements are such as C, S, O, N, etc. Preferably, T includes Fe and / or Ti.

[0037] The present invention also provides a method for preparing the above-mentioned NdFeB magnet, the method comprising:

[0038] (a) Melting process: melting, casting and cooling the above magnet components to form alloy sheets;

[0039] (b) Powdering process: crushing the alloy flakes into alloy powder;

[0040] (c) Pressing step: pressing the alloy powder under the action of a magnetic field to obtain a green body;

[0041] (d) Sintering process: The green body is subjected to sintering treatment and aging treatment to prepare a NdFeB magnet.

[0042] According to the embodiment of the present invention, the smelting process of step (a) is a conventional technology in the prior art, such as preparing alloy sheets by a belt-spinning method; illustratively, the step (a) is specifically a smelting process: according to the ratio of the target components, the components of the magnet are fully melted into alloy steel liquid in a medium frequency induction melting furnace under vacuum or inert gas atmosphere, and then rapidly cooled to form alloy sheets or alloy ingots. Exemplarily, it is secondary cooling.

[0043] According to an embodiment of the present invention, the step (b) is specifically a powder making process: including coarse crushing and fine crushing, preferably, the coarse crushing is selected from hydrogen embrittlement and / or medium grinding.

[0044] Preferably, the fine crushing is selected from air jet milling. Preferably, the air jet milling is carried out under an inert gas atmosphere. Preferably, the inert gas is selected from nitrogen, helium, etc.

[0045] In the present invention, the hydrogen embrittlement, intermediate grinding or air flow grinding can be performed by operations known in the prior art.

[0046] According to an embodiment of the present invention, in step (b), after fine crushing, it is also obtained by screening, for example, by screening with a grading wheel. Exemplarily, the SMD particle size of the alloy powder is 1.8-8μm, preferably 2.5-6μm, and X90 / X10≤4.5. Wherein, SMD is the area average particle size, the smaller the SMD, the smaller the particle size of the powder particles, the larger the SMD, the larger the particle size of the powder particles; X90 represents the particle size value corresponding to the cumulative distribution percentage reaching 90%, that is, the particle size of all particles is not greater than this particle size, and the number of particles greater than this particle size value is 0, X10 represents the particle size value corresponding to the cumulative distribution percentage reaching 10%, that is, the particle size of all particles is not greater than this particle size, and the number of particles greater than the secondary particle size value is 0; X90 / X10 refers to the particle size distribution of the powder, and the smaller the X90 / X10, the more concentrated the particle size distribution of the powder is.

[0047] According to an embodiment of the present invention, in step (b), a lubricant needs to be added during fine crushing, preferably before and after the jet mill. Adding a lubricant before the jet mill can improve the fluidity of the powder; adding it during the jet mill can improve the fluidity and uniformity of the powder; adding a lubricant after the jet mill can also improve the uniformity and fluidity of the powder, facilitating uniform powder filling and pressing.

[0048] Preferably, the lubricant is selected from known reagents in the prior art, and the known amount in the prior art group is used to achieve sufficient mixing of the powder and easy molding. Exemplarily, the lubricant is selected from volatile organic solvents such as lipids or alcohols, such as zinc stearate. Exemplarily, the amount of the lubricant added is 0.1-1wt% of the total mass of the raw materials.

[0049] Preferably, after adding the lubricant, mixing is also required. Preferably, the mixing time is 1-6 hours.

[0050] The mixing in the present invention can be carried out by a method known in the prior art, such as placing the materials in a mixer for mixing.

[0051] According to an embodiment of the present invention, in step (c), the compression molding is performed in a press mold cavity.

[0052] According to an embodiment of the present invention, in step (c), before compression molding, orientation magnetization and molding need to be carried out at a magnetic field strength of more than 2T, and coil magnetization or pulse magnetization can be used.

[0053] According to an embodiment of the present invention, in step (c), after the press molding, a reverse magnetic field is applied for demagnetization.

[0054] According to an embodiment of the present invention, in step (c), the formed green body may also be processed in a cold isostatic press to further increase the green body density.

[0055] According to an embodiment of the present invention, in step (d), before sintering, the green body is also subjected to heat treatment, the heat treatment temperature is 100-950°C, preferably 150-900°C, the heat treatment insulation time is 60-120min, illustratively, the heat treatment temperature is 3-6 sections, the insulation temperature of each section of the heat treatment can be the same or different, the insulation time can be the same or different, and the heat treatment stage can be carried out under inert gas or under vacuum. Exemplarily, the heat treatment temperature is 4 sections, respectively 100-200°C, 200-550°C, 550-700°C, 700-950°C.

[0056] According to an embodiment of the present invention, in step (d), the sintering treatment has more than three sintering insulation stages and a heating stage before sintering insulation, exemplarily 3-10 stages, such as 3, 4, 5, 6, 7, 8, 9 or 10 stages, the temperature of the sintering insulation stage is 950-1200°C, preferably 980-1070°C, and the insulation time of each stage is 20-120min; the insulation temperature of each stage of the sintering treatment can be the same or different, the insulation time can be the same or different, and the sintering insulation stage can be carried out under inert gas or under vacuum.

[0057] For example, during each stage of sintering treatment, the heating rate is 0.5-5°C / min; more preferably 1-4°C / min. The heating rate of each stage of heating can be the same or different.

[0058] According to the implementation scheme of the present invention, between each two adjacent sintering and heat preservation processes, the next heating and heat preservation process can be directly carried out after the previous sintering and heat preservation stage is completed, or after the previous sintering and heat preservation stage is completed, cooling is first carried out, and then the next heating and heat preservation process is carried out. There is no limit on the cooling temperature, which can be lower than the temperature of the previous sintering and heat preservation stage. There is no special limit on the number of cooling stages, as long as the required cooling temperature is reached; that is, between each two adjacent sintering and heat preservation processes, the process can be any random. For example, after the previous sintering and heat preservation stage is completed, 1-10 stages of cooling are carried out first, and then the next heating and heat preservation process is carried out. The temperatures of 1-10 stages of cooling can be the same or different.

[0059] In order to ensure production efficiency, it is preferred that the sintering and heat preservation stages be controlled within 10 groups.

[0060] In the present invention, the above three or more sintering and heat-insulating steps are adopted to achieve uniform distribution of elements such as Cu, Ga, and Al. This sintering mode helps to segregate elements such as Cu, Ga, and Al from the grain boundary phase to the main phase grains.

[0061] According to an embodiment of the present invention, in step (d), the aging treatment is performed after the sintering treatment is cooled. Exemplarily, the aging treatment includes: after the sintering is completed, cooling to room temperature, and then heating treatment.

[0062] Preferably, the aging treatment is selected from a primary aging treatment or a secondary aging treatment.

[0063] Preferably, the conditions of the primary aging treatment are: the aging treatment temperature is 500-700°C, and the holding time is 240-420min. Preferably, the secondary aging treatment includes: heating for the first aging treatment, the first aging treatment temperature is 800-950°C, and the holding time is 180-300min; cooling to below 200°C, and then heating for the second aging treatment, the second aging treatment temperature is between 450-600°C, and the holding time is 240-360min.

[0064] According to an embodiment of the present invention, a diffusion treatment may be further performed after the sintering process.

[0065] Preferably, the diffusion treatment includes applying diffusion material to the surface of the magnet, and performing vacuum heating diffusion treatment, diffusion cooling and diffusion aging treatment.

[0066] Preferably, the diffusion material is selected from at least one of pure metal of Dy and / or Tb, hydride of Dy and / or Tb, oxide of Dy and / or Tb, hydroxide of Dy and / or Tb, fluoride of Dy and / or Tb and other alloys, exemplified by Dy metal.

[0067] Preferably, the diffusion treatment can be performed by vacuum evaporation, magnetron sputtering, coating or burying.

[0068] Preferably, the temperature of the vacuum heating diffusion treatment is 850-950° C., and the time of the vacuum heating diffusion treatment is 10-30 hours.

[0069] Preferably, the temperature of the diffusion cooling is below 100°C.

[0070] Preferably, the temperature of the diffusion aging treatment is 450-600° C., and the time of the diffusion aging treatment is 4-8 hours.

[0071] According to an embodiment of the present invention, after the sintering process and before the diffusion treatment, the green body may be processed into a target size.

[0072] According to an embodiment of the present invention, after the sintering process and before the diffusion treatment, the green body is processed into a target size and then the magnet is subjected to a surface cleaning treatment to eliminate machining debris, machining cutting fluid residues or machining glue on the magnet surface.

[0073] According to the implementation scheme of the present aspect, the cleaning treatment before diffusion can be, but not limited to, pure water ultrasonic cleaning, acid cleaning, etc., and the acid can be, but not limited to, nitric acid, sulfuric acid, citric acid, etc.

[0074] The present invention also provides application of the above-mentioned NdFeB magnet for use in motors.

[0075] The present invention also provides a motor, comprising the above-mentioned magnet.

[0076] The present invention also provides applications of the above motor. Preferably, the motor can be used in new energy vehicles and energy-saving home appliances.

[0077] Beneficial effects of the present invention:

[0078] The present invention can obtain higher Br and Hcj of the magnet by regulating the composition ratio of elements such as Cu, Ga, Al and their distribution in the magnet, as well as the grain size. The sintering treatment method provided by the present invention, i.e., more than three sintering and heat preservation stages and a heating stage before heat preservation, can ensure that the main phase grains and grain boundary phases of the magnet are fully sintered and the density is improved, while suppressing the abnormal growth of the main phase grains, and avoiding the deflection of the oriented orderly grains during sintering, ensuring the orientation degree of the magnet, and significantly improving the Br of the magnet.

[0079] In the present application, within the range of the atomic concentration ratio of Cu, Ga and Al (i.e., 1≤[Cu2] / [Cu1]<2, 1≤[Ga2] / [Ga1]<2, 1<[Al2] / [Al1]<2), R2(Fe,M) is formed in the main phase grains. 14 B structure, and the M enrichment in the two grain boundaries where the main phase grains contact is relatively low, while obtaining a higher Hcj, it can still maintain a higher remanence. And after diffusion treatment, the Hcj improvement effect is significant, and the diffusion of Tb can achieve an Hcj improvement of ≥880kA / m, and the diffusion of Dy can achieve an Hcj improvement of ≥480kA / m. BRIEF DESCRIPTION OF THE DRAWINGS

[0080] Figure 1 This is a schematic diagram of the distribution of Cu in the magnet in Example 1.

[0081] Figure 2 This is a schematic diagram of the distribution of Cu in the magnet in Comparative Example 1. DETAILED DESCRIPTION

[0082] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0083] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0084] Example 1-2

[0085] A method for preparing a neodymium iron boron magnet, the method comprising the following steps:

[0086] (a) Raw materials were prepared according to the target composition of the magnet in Table 1 below, and smelted in a vacuum induction melting furnace under the protection of Ar gas atmosphere. The molten liquid was cast onto a quenching roller with a rotation speed of 33 rpm and a casting temperature of 1420°C (i.e., strip casting process) to prepare NdFeB alloy sheets with an average thickness of 0.22 mm.

[0087] Table 1 Target components of the magnets of the embodiment (mass percentage)

[0088] serial number Pr Nd B Co Cu Ga Al Ti Fe and impurity elements Example 1 - 31 0.98 1 0.3 0.2 0.3 0.2 margin Example 2 6 25 0.97 1 0.2 0.4 0.5 0 margin

[0089] (b) The alloy flakes are coarsely crushed by hydrogen embrittlement process to obtain powder, and zinc stearate is added as lubricant in an amount of 0.1wt% of the raw material to the powder, and the mixture is mixed for 60 minutes. The mixed material is finely crushed in a fluidized bed jet mill, and nitrogen is used as the grinding gas. The target particle size SMD = 2.5 μm of jet mill powder (i.e., alloy powder) is obtained by adjusting equipment parameters such as the rotating speed of the classifying wheel and the grinding pressure, and X90 / X10 is 4.2.

[0090] (c) The jet milled powder of the target particle size was added with 0.2 wt% zinc stearate as a lubricant based on the mass of the raw material, and the mixture was mixed for 120 min. After sufficient mixing, the mixture was pressed into a green body under a charging magnetic field of 2 T, and then subjected to isostatic pressing at a pressure of 180 MPa for 15 s in an isostatic press to improve the green body density, and a green body density of 4.3 g / cm was obtained. 3 of the pressed billet.

[0091] (d) The green body is placed in a sintering furnace and subjected to a heating treatment in a vacuum atmosphere. The green body is subjected to a delubricant treatment by being kept at 150°C and 260°C for 100 minutes respectively, and a degassing treatment by being kept at 600°C and 900°C for 90 minutes respectively. Then, a three-stage sintering and heat-keeping process as shown in Table 2 is performed. After the third stage of sintering and heat-keeping is completed, the green body is directly cooled to room temperature to obtain a sintered body. The specific three-stage heating and heat-keeping sintering process is shown in Table 2, and after each sintering and heat-keeping stage is completed, the temperature is directly raised to proceed to the next heating process.

[0092] Table 2 3-stage heating and holding sintering process parameters of the magnet of the embodiment

[0093]

[0094] (e) Secondary aging treatment: Take the above sintered body, heat it to 900°C and keep it for 180 min, then cool it to 200°C, and then heat it to 530°C and keep it for 240 min. After the end of the heat preservation, cool it to room temperature to obtain a magnet after aging treatment.

[0095] (f) The magnet processing standard after aging treatment The magnetic properties of the sample column were tested using a BH instrument. The specific magnetic properties test results are shown in Table 3.

[0096] Table 3 Magnetic properties test data of the magnets of the embodiment

[0097] Br(T) Hcj(kA / m) Hk(kA / m) Hk / Hcj Example 1 1.354 1543 1521 0.986 Example 2 1.362 1473 1460 0.991

[0098] The vertical orientation surface of the magnet prepared in Example 1-2 was polished, and the size of the magnet grains was confirmed by scanning electron microscope SEM. The average grain size in the field of view (*2000 times) was defined by Image-Pro Plus software analysis, and the grain size of the largest grain in the field of view was defined as the maximum grain size. In the field of view of *2000 times, the number of grains was counted, and the unit grain area was taken as the field area divided by the number of grains, and the grain size was calculated according to the circle area formula as the average grain size; the grain with the largest area in the field of view was taken, and the grain size was calculated according to the circle area formula as the maximum grain size. The test results are shown in Table 4.

[0099] Field emission electron probe microanalyzer (FE-EPMA) (JEOL, 8530F) was used to analyze and confirm the distribution of each component in the magnet. Line scanning was performed through the main phase grains, two-grain grain boundaries, and triangular grain boundaries to confirm and analyze the different distribution concentrations of elements such as Cu, Ga, and Al in the above-mentioned areas. The atomic concentrations of Cu, Ga, and Al at 0.5 μm from the two-grain boundary into the main phase grains were defined as [Cu1], [Ga1], and [Al1], respectively. The atomic concentrations of Cu, Ga, and Al at the center of the two-grain boundary between two main phase grains were defined as [Cu2], [Ga2], and [Al2], respectively. The average value of the ratio of 5 groups of adjacent main phase grains and two-grain boundaries in the field of view was taken to define [Cu2] / [Cu1]. The concentration ratio of the two was used to confirm whether the Cu element was relatively evenly distributed in the main phase grains and two-grain boundaries. In the triangular grain boundary, the area where the Cu element concentration satisfies [Cu3] / [Cu1]≥2 is defined as the Cu-rich area. The ratio of the area of ​​the Cu-rich area to the total area of ​​the grain boundary phase is calculated using Image-Pro Plus software. The relative distribution of Ga and Al and the area ratio of the enriched area are analyzed using the same test analysis method.

[0100] The distribution and structural characteristics of Cu, Ga and Al tested by the above analysis method are shown in Table 4:

[0101] Table 4 Particle size and element distribution data of the magnets of the embodiment

[0102]

[0103] Figure 1 is a schematic diagram of the distribution of Cu in the magnet in Example 1, Figure 1It can be seen that Cu is relatively evenly distributed on the surface of the main phase grains and at the boundaries between the two grains. Although there are Cu-rich regions at the triangular grain boundaries, the area of ​​the Cu-rich regions is small, and its enrichment in the triangular grain boundaries is also relatively low.

[0104] Comparative Example 1-2

[0105] (a) Raw materials were prepared according to the target composition of the magnet in Table 5 below, and NdFeB alloy sheets were prepared by strip casting process. The average thickness of the target alloy sheet was 0.22 mm.

[0106] Table 5 Target components of comparative magnets (mass percentage)

[0107] serial number Pr Nd B Co Cu Ga Al Ti Fe and impurity elements Comparative Example 1 - 31 0.98 1 0.7 0.2 0.3 0.2 margin Comparative Example 2 - 31 0.98 1 0.3 0 0 0 margin

[0108] The alloy flakes are crushed and powdered using the same process as in Example 1-2, and the alloy powder is pressed into shape. The sintering process is performed according to the three-stage heating and insulation sintering process in Table 6 below, and the temperature is directly increased after each sintering and insulation stage to proceed to the next heating process. After the third insulation stage, the alloy is cooled to room temperature to obtain a sintered body.

[0109] Secondary aging treatment: Take the above sintered body, heat it to 900°C and keep it for 180 minutes, then cool it to 200°C, then heat it to 530°C and keep it for 240 minutes, and then cool it to room temperature to obtain the magnet after aging treatment.

[0110] Table 6 Comparison of the three-stage heating and holding sintering process parameters of the magnet

[0111]

[0112] The magnetic properties were tested according to the above magnetic properties test method, and the test results are shown in Table 7. The magnet grain size test and element distribution test methods were used, and the results are shown in Table 8:

[0113] Table 7 Magnetic properties test data of comparative magnets

[0114] Br(T) Hcj(kA / m) Hk(kA / m) Hk / Hcj Comparative Example 1 1.293 1320 1229 0.931 Comparative Example 2 1.41 1135 1069 0.942

[0115] Table 8 Particle size and element distribution data of comparative magnets

[0116]

[0117] *Since Ga and Al were not added to the magnet design components of Comparative Example 2, “--” indicates that no comparison of component concentrations was performed.

[0118] Figure 2 This is a schematic diagram of the distribution of Cu in the magnet in Comparative Example 1. Figure 2It can be seen that although the Cu enrichment degree of the main phase grain surface and the two grain boundaries is low, compared with Figure 1 The relative concentration is still higher at the two-grain boundary, and the Cu-rich area in the triangular grain boundary increases significantly, accounting for a high area, that is, Cu is highly enriched in the triangular grain boundary.

[0119] By comparing Example 1-2 with Comparative Example 1-2, although the Br of Comparative Example 2 is improved to a certain extent compared with the Br of Example 1-2, the coercive force Hcj is much reduced, and the squareness is also much reduced. When the components of the magnet are within the scope of the present invention, the comprehensive performance of Br and Hcj is better, and the squareness Hk / Hcj is excellent, which can ensure the stable magnetic field output of the magnet.

[0120] Example 3

[0121] The difference between Example 3 and Example 1 is that in step (d), the sintering process is performed according to the three-stage heating and heat preservation sintering process in Table 9 below, and after each stage of sintering and heat preservation, it is cooled to 900° C. before the next stage of heating is performed.

[0122] Table 9 Comparison of the three-stage heating and holding sintering process parameters of the magnet

[0123]

[0124] Comparative Example 3

[0125] The difference between Comparative Example 3 and Example 1 is that step (d) is sintered according to the two-stage heating and insulation sintering process in Table 10 below, and after the first insulation stage is completed, it is cooled to 400° C. before the second stage of heating is performed.

[0126] Table 10 Two-stage heating and holding sintering process parameters of the magnet of comparative example 3

[0127]

[0128] The magnets prepared in Example 3 and Comparative Example 3 were subjected to magnetic property testing, magnet grain size and element distribution analysis. The magnetic property test results are shown in Table 11, and the grain size and element distribution are shown in Table 12.

[0129] Table 11 Magnetic properties test data of the magnets of Example 3 and Comparative Example 3

[0130]

[0131] Table 12 Particle size and element distribution data of magnets of Example 3 and Comparative Example 3

[0132]

[0133] By comparing Example 3 with Comparative Example 3, the temperature-raising and heat-insulating sintering process of the present invention has a shorter cycle and better magnetic properties than the traditional two-stage sintering process, effectively suppresses the abnormal growth of magnet grains, and achieves uniform distribution of Cu, Ga, and Al elements in the main phase grains and the boundaries between the two grains, reducing their enrichment in the triangular grain boundaries.

[0134] Compared with Example 1, Example 3 adds cooling to below 900°C after each heating and insulation before the next heating stage. The sintering process with three heating and cooling intervals is adopted to further effectively inhibit the abnormal growth of magnet grains, and the magnet performance is also improved to a certain extent.

[0135] Example 4

[0136] The sintered and aged magnet of Example 3 was processed into a thin sheet product with a length of 20 mm, a width of 20 mm, and a thickness of 5 mm. A layer of metal Dy film was applied on the surface of the magnet by a dipping process, and then the magnet was subjected to diffusion treatment at 900°C for 15 hours. After the diffusion temperature was cooled to below 100°C, the temperature was raised to 500°C for 5 hours of aging treatment. The magnetic properties of the final magnet were tested, and the test results are shown in Table 13 below.

[0137] Comparative Example 4

[0138] Take the magnet after sintering and aging of Comparative Example 3, and adopt the same diffusion treatment process as Example 4, that is, process the magnet into a thin sheet product with a length of 20 mm, a width of 20 mm, and a thickness of 5 mm, and apply a layer of metal Dy film on the surface of the magnet by dipping process, and then carry out diffusion treatment at 900°C for 15 hours, and after the diffusion temperature is cooled to below 100°C, it is heated to 500°C for aging treatment for 5 hours. The final magnet is tested for magnetic properties, and the test results are shown in Table 13 below.

[0139] Table 13 Magnetic properties after diffusion of Example 4 and Comparative Example 4

[0140]

[0141] In Table 13, △Br and △Hcj refer to the Br increase and Hcj increase of Example 4 relative to Example 3, and the Br increase and Hcj increase of Comparative Example 4 relative to Comparative Example 3, respectively.

[0142] By comparing the results of Example 4 and Comparative Example 4, it can be seen that the magnet prepared by the method of the present invention has a better diffusion Hcj increase by using the same diffusion process, and the final magnet performance is better, and its organizational structure is more suitable for diffusion.

[0143] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high performance NdFeB magnet, characterized in that: The magnet includes R2 (Fe, M) 14 Main phase grains and grain boundary phases of B structure; the grain boundary phase comprises two grain boundaries between two main phase grains, and a triangular grain boundary composed of gaps between three or more main phase grains; wherein M comprises Cu, Ga and / or Al, and R is at least one rare earth element including Nd; The atomic concentration of Cu in adjacent main phase grains is set as [Cu1], and the atomic concentration of Cu in the boundary between two grains is set as [Cu2], which satisfies the relationship of 1≤[Cu2] / [Cu1]<2; The triangular grain boundary in the magnet contains a Cu-rich region, and the atomic concentration of Cu in the triangular grain boundary is set to [Cu3], which satisfies the relationship [Cu3] / [Cu1]≥2; The atomic concentration of Ga in adjacent main phase grains is set as [Ga1], and the atomic concentration of Ga in the boundary between two grains is set as [Ga2], which satisfies the relationship of 1≤[Ga2] / [Ga1]<2; The triangular grain boundary in the magnet contains a Ga-rich region, and the atomic concentration of Ga in the triangular grain boundary is set to [Ga3], which satisfies the relationship [Ga3] / [Ga1]≥2; The atomic concentration of Al in adjacent main phase grains is set as [Al1], and the atomic concentration of Al in the boundary between two grains is set as [Al2], which satisfies the relationship of 1<[Al2] / [Al1]<2; The triangular grain boundary in the magnet contains an Al-rich region, and the atomic concentration of Al in the triangular grain boundary is set to [Al3], which satisfies the relationship [Al3] / [Al1]≥2; The Cu-rich area of ​​the triangular grain boundary accounts for less than 5% of the total area of ​​the grain boundary phase; The Ga-rich region area at the triangular grain boundary accounts for less than 5% of the total grain boundary phase area; The Al-rich region area at the triangular grain boundary accounts for less than 5% of the total grain boundary phase area; The NdFeB magnet, calculated by mass ratio as 100%, includes the following components: 27-35% R; R is at least one rare earth element including Nd; 0.8-1.2wt% B; 0-3.0wt% Co; 0.1-0.6wt% Cu; 0.1-0.8wt% Ga; 0-1.0wt% Al; 60-72wt% T: T includes Fe and other transition metal elements, and inevitable impurity elements.

2. The magnet according to claim 1, characterized in that The average grain size of the main phase of the magnet is 1.8-8μm.

3. The magnet according to claim 1, characterized in that The grain boundary phase in the Ga-rich region is a non-ferromagnetic phase.

4. The magnet according to claim 1, characterized in that Adjacent main phase grains refer to main phase grains adjacent to the two-grain grain boundary.

5. The magnet according to claim 1, characterized in that The high-performance NdFeB magnet also includes a transition metal element, which is at least one of Mn, Si, Zr, Ti, and Nb.

6. The method for preparing a magnet according to any one of claims 1 to 5, characterized in that: The method comprises: (a) Melting process: melting, casting and cooling the above magnet components to form alloy sheets; (b) Powdering process: crushing the alloy flakes into alloy powder; (c) Pressing process: pressing the alloy powder under the action of a magnetic field to obtain a green body; (d) Sintering process: the green body is subjected to sintering treatment and aging treatment to prepare a NdFeB magnet; In step (d), the sintering process has more than three sintering and heat preservation stages and a heating stage before sintering and heat preservation. The temperature of the sintering and heat preservation stages is 950-1200° C., and the heat preservation time of each stage is 20-120 minutes.

7. The method according to claim 6, characterized in that In step (b), the alloy powder has a SMD particle size of 1.8-8 μm, and X90 / X10≤4.

5.

8. The method according to claim 6, characterized in that In step (b), the sintering process comprises 3 to 10 stages of sintering heat preservation and a heating stage before sintering heat preservation.

9. The method according to claim 6, characterized in that In step (b), during each sintering process, the heating rate is 0.5-5°C / min.

10. The method according to claim 6, characterized in that In step (b), between each two adjacent sintering and heat preservation processes, the next heating and heat preservation process is directly carried out after the previous sintering and heat preservation stage is completed, or after the previous sintering and heat preservation stage is completed, cooling is first carried out and then the next heating and heat preservation process is carried out, that is, between each two adjacent sintering and heat preservation processes, the process is random.

11. The method according to claim 6, characterized in that The aging treatment is selected from a primary aging treatment or a secondary aging treatment; The conditions of the primary aging treatment are: the aging treatment temperature is 500-700°C, and the holding time is 240-420min; The secondary aging treatment includes: heating for the first aging treatment, the first aging treatment temperature is 800-950°C, and the heat preservation time is 180-300min; cooling to below 200°C, and then heating for the second aging treatment, the second aging treatment temperature is between 450-600°C, and the heat preservation time is 240-360min.

12. The method according to claim 6, characterized in that After the sintering process, a diffusion treatment is also performed.

13. The method according to claim 12, characterized in that The diffusion treatment includes applying diffusion material on the surface of the magnet, performing vacuum heating diffusion treatment, diffusion cooling and diffusion aging treatment.

14. The method according to claim 13, characterized in that The diffusion material is selected from at least one of pure metal of Dy and / or Tb, hydride of Dy and / or Tb, oxide of Dy and / or Tb, hydroxide of Dy and / or Tb, and fluoride alloy of Dy and / or Tb.

15. Use of the magnet according to any one of claims 1 to 5, characterized in that: Used on motors.

16. The use according to claim 15, characterized in that Used in new energy vehicles or energy-saving home appliances.

Citation Information

Patent Citations

  • R-t-b rare earth sintered magnet

    CN102693812A

  • Magnetic body

    CN103282976A

  • Sintering method of neodymium-iron-boron magnet

    CN106252012A

  • R-(Fe, Co)-B sintered magnet and making method

    CN106710766A